Agricultoras na construção de Sistemas Agroindustriais Familiares Ecológicos (SAFEs) no Paraná - Demetrio, Milena (2024)
This article discusses the contributions of women farmers in adding value to food produced in Ecological Family Agro-Industrial Systems (SAFEs) in the southwest of Paraná (BR). SAFEs are part of agri-food networks that are alternatives to the hegemonic food system, offering artisanal, ecological, and cultural foods marketed through short chains. In this context, women are the ones who consume the healthiest food and seek sustainable production. Despite the importance of women farmers' work, part of their working day is disregarded because it does not generate direct monetary value. Using the topical life history method, the contribution of women to the creation and functioning of SAFEs was analyzed in both the productive and reproductive dimensions. The results showed that women significantly contribute to all the SAFEs' activities and are primarily responsible for domestic work.